The Impact of Learning Models for Explicit Instruction on Student Learning Outcomes in Vocational High School 2 Banda Aceh - Zul Fajjeri; Hari Anna Lastya; Hadi Kurniawan (PTE FTK UIN Ar-Raniry, 2024)
The Explicit Instruction learning model is a learning model that positions the teacher as a facilitator and organizer in the learning process. This research aims to see the effect of the explicit instruction learning model in improving student learning outcomes in the Basic Passive Electronic Components subject. This research uses a quantitative type method with an experimental approach (one group pretest-posttest design) using pre-test and post-test question sheet instruments. The research subjects consisted of 25 students of class X Electronics Engineering at SMKN 2 Banda Aceh. The research results showed that the application of the explicit instruction learning model had an effect on the learning outcomes of students at SMK N 2 Banda Aceh as evidenced by the post-test results which increased by 44 points. This shows a positive change in student learning outcomes. Based on the research results, it can be concluded that the application of the explicit instruction learning model has an effect and can improve student learning outcomes at SMK N 2 Banda Aceh.